2002
DOI: 10.1046/j.1526-4610.2002.02203.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the Prophylactic Treatment of Migraine Without Aura: A Comparison with Flunarizine

Abstract: Acupuncture proved to be adequate for migraine prophylaxis. Relative to flunarizine, acupuncture treatment exhibited greater effectiveness in the first months of therapy and superior tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 15 publications
(19 reference statements)
11
104
1
Order By: Relevance
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…Effects found in this study that have been previously reported include: differences between acupuncture and control for migraine 7,12,45 that increased between posttreatment and 1-year follow-up, 11 unconvincing effects for tension-type headache, [46][47][48][49] improvements in severity and frequency, 24 and increased benefit in patients with greater headache severity.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…There were no differences between sham acupuncture and ordinary acupuncture in the treatment of patients for migraine, but both groups were more effective than a waiting list control (7). Acupuncture reduced the frequency of migraine attacks and had the best outcome over time when compared with those from TENS and laser therapy (8). Persons with chronic headache, predominantly migraine, suffered form a significantly reduced number of headaches through acupuncture treatment in addition to standard care, when compared with only standard care (5).…”
Section: Introductionmentioning
confidence: 92%
“…h. Superficial needling has been advocated as a treatment technique in its own right [11][12][13] i. Sham acupuncture has been proven to be as effective as verum acupuncture and dedicated analgesics, in headache and migraine [14][15][16][17] j. Sham acupuncture and verum acupuncture have been shown to be more effective than conventional therapeutic interventions in low back pain 18 k. Sham ('placebo') acupuncture was associated with a significantly higher overall pregnancy rate when compared with real acupuncture in IVF treatment. 8 Because of the need to conduct high quality RCTs examining the effects of acupuncture that meet the conventions of good design, different sham acupuncture procedures have been introduced.…”
Section: Review and Analysismentioning
confidence: 99%